MORPHOLOGIC AND MORPHOMETRIC ASPECTS OF ENOCYTES OF APIS-MELLIFERA QUEENS AND WORKERS IN DIFFERENT PHASES OF LIFE - Ruvolo, MCC; Landim, C. D. (Mem Inst Oswaldo Cruz, 1993)
Oenocytes of adult workers and queens of Apis mellifera L. were studied in different ages or life stages, by means of morphometric and histologic techniques. In workers, the oenocytes were found in the head, near the mandibles and in the abdomen, immersed in the parietal fat body mainly below the sterna, close to the wax glands. In queens, two populations of oenocytes different in size and localization were found within the parietal and visceral fat body, respectively. The oenocytes of workers and queens show the presence of acid lipids and acid phosphatase. The role of these cells in the castes differences is discussed.
Keywords: ENOCYTES; APIS-MELLIFERA; MORPHOLOGY; DEVELOPMENT; CASTES DIFFERENCES; FAT BODY